2020
DOI: 10.1007/s13369-020-04573-9
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Film Cooling Due to Simple/Compound Angle Hole Combination

Abstract: Film cooling technique is one of the gas turbine components saving from thermal failure. This article presents a numerical study of film cooling effectiveness due to two rows of simple and compound angle holes. The holes are inclined with 30° on a flat surface for all studied cases. Two orientation angles of the film cooling holes are applied (0° and 30°). Six cases are used to represent different configurations for the two rows. Three different values of velocity ratios (namely 0.5, 1.0 and 2.0) are represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The discrete hole with a cylindrical shape was suggested as the appropriate one and then commonly applied in practice due to its simplicity and lower manufacturing cost. The early studies [2][3][4][5] revealed that the blowing ratio significantly influences the cylindrical hole's cooling performance. They concluded that the effectiveness tends to increase with the increase of blowing ratio when the blowing ratio is lower than 0.5 but deteriorates sharply when the blowing ratio exceeds 0.5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discrete hole with a cylindrical shape was suggested as the appropriate one and then commonly applied in practice due to its simplicity and lower manufacturing cost. The early studies [2][3][4][5] revealed that the blowing ratio significantly influences the cylindrical hole's cooling performance. They concluded that the effectiveness tends to increase with the increase of blowing ratio when the blowing ratio is lower than 0.5 but deteriorates sharply when the blowing ratio exceeds 0.5.…”
Section: Introductionmentioning
confidence: 99%
“…cooling effectiveness profile Fig.4Grid independence test for the cratered hole with arc protrusion at M=0 5. …”
mentioning
confidence: 99%
“…Most research has been done by the RANS approach with the k –ε $\varepsilon $ turbulence method to simulate the film cooling of the typical blades 12 . The main parameters involved in the film cooling phenomena (blowing ratio, turbulence intensity, hole angle, hole geometry, in stagger and in‐line hole arrangement, hole to hole distance, coolant velocity, and temperature) are examined in various studies 13–25 …”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the film cooling efficiency was significantly enhanced by changing a single hole with a multi‐hole shape. Abdelmohimen et al 21 numerically investigated the effect of film cooling on a flat plate by applying two rows of simple and compound angle holes in stagger an in‐line arrangement. They found that applying compound angle holes with in‐line configuration increase the film cooling performance but applying it in staggered configuration at a high‐velocity ratio decrease the film cooling performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation